Next Generation Cargo Bike for Park & City Maintenance - Elmdahl,Johan (2025)
In this thesis, I present the full design process of developing a cargo bike concept aimed at improving the work environment for park and city maintenance workers, using Velove’s cargo bike as the baseplate. I worked in close collaboration with Lunds Kommun and their park maintenance workers to get first-hand knowledge about how the current products are used and how my project could fit into their workflow. This project addresses some of the inefficiencies I found in the park maintenance organization, such as the disorganization of tools in vehicles, safety concerns on current cargo bikes and the lack of a workforce with a driver’s license, by giving them an alternative to driving a van. A holistic development strategy was used, incorporating extensive interviews with multiple stakeholders, field testing, and user-driven iterative prototyping. The final concept resulted in an easily repairable and adaptable product that can grow with the organization and be tailored to meet evolving task requirements. The concept could work as a replacement for larger vans in cities and gives the user more freedom and responsibility, since they would have their own vehicle and tools to take care of.
Keywords: Mobility; Micro-mobility; Bikes; Cargobike; Park Maintenance; Parks; Maintenance; Design